Effect of Ethylene Glycol on Structural Integrity at Each Stage of Preantral Follicle Development Post Vitrification of Rat Ovary-Histological Analysis - Nova Anita; Abinawanto Abinawanto; Ahmad Aulia Jusuf; Anom Bowolaksono; Huriyah Adani Saoemi (Bogor Agricultural University, Indonesia, 2021)
The structure of follicular tissue affects the ability to maintain the structural integrity of follicles against cryoinjury post-vitrification. Histological analysis was conducted on the structural integrity of each stage of preantral follicles post-vitrification using 7.5% and 15.0% doses of ethylene glycol (EG), and ovarian sections with HE staining were observed using an Olympus CX21 microscope connected to Optilab 3.0 lens and Image Raster software. Analysis was conducted on the ovarian cortex in the tracing line area using polygon measure tools to obtain follicle density (follicles/mm2) and follicle index (%) data. The result showed that the EG group 7.5% (KP1) increased follicle density compared to the vitrified group (KKV) in primordial (15.83±1.77) and primary (22.94±8.51) stages. Meanwhile, KP2 (EG 15%) was in primordial (41.92±6.45), primary (11.69±1.95), secondary (33.48±3.63), and tertiary (5.93±0.69) stages. KP1 increased grade 3 follicle index compared to KKV in primary (27.66±2.34), secondary (32.41±6.99), and tertiary (25.00±5.00) stages. Meanwhile, KP2 was in primary (26.87±6.68) and tertiary (25.00±5.00) stages. Both doses of 7.5% and 15.0% EG were able to maintain structural integrity at certain stages of preantral follicles. Secondary and tertiary follicles are the best stages in maintaining grade 3 follicular integrity with the addition of 7.5% EG.